Expanding Border Temporalities: Toward an Analysis of Border Future Imaginations - Gerst, Dominik; Krämer, Hannes (Borders in Globalization Review, 2024)
Even though questions about the future have played a central role in recent times of polycrisis, border studies have long been relatively silent about the future. Our article develops a research perspective through which the sensitization of border research for the temporal dimension of the future can be achieved. To this end, social and cultural studies’ perspectives on the future are mobilized to approach the interplay of borderwork and/as futurework. We develop a foundation for an analysis of what we call “border future imaginations”. In this way, this study expands our understanding of border temporalities with reference to the future orientation of contemporary societies. Keywords: border temporalities; future; borderwork; futurework; sociology of time.